Carqueja and Tola High-Andean Plants - Peru: Approximation of Their Bioactive Compounds in Aqueous and Ethanolic Extract - Quispitupa Ramos, Edison (2026)
Carqueja (Baccharis trimera) and Tola (Parastrephia lepidophylla) plants are used by inhabitants to alleviate different ills. This study evaluates total polyphenols, antioxidant activity, and flavonoids in the aqueous and ethanolic extracts. Tola exhibited a higher concentration of total polyphenols compared to Carqueja in ethanolic extracts (350.065 and 56.355 mg of Gallic Acid/g DW, respectively). The ethanolic extract of Tola showed superior antioxidant activity, as evidenced by DPPH and ABTS assays with mean 46.165 mg Trolox Equivalent/g DW (20 g/200 mL 80% ethanol) and 249.815 mg Trolox Equivalent/g DW (15 g/200 mL 80% ethanol), respectively. Carqueja showed lower values in both analyses. The ratio (20 g/200 mL) of the ethanolic extract of Tola demonstrated a mean of 298.86 mg of Quercetin equiv/g DW in total flavonoids. Additionally, HPLC analysis detected the presence of chlorogenic acid and quercetin, phenolic acids that may contribute to the observed antioxidant activity. FTIR spectra revealed characteristic peaks indicating the presence of phenolic compounds associated with proteins and carbohydrates in both plant extracts. In conclusion, the ethanolic extracts of Carqueja and Tola exhibit significant levels of total polyphenols, antioxidant activity, and total flavonoids, highlighting their potential as sources of bioactive compounds.